Information and communication technologies and access to maternal and child health information: Implications for sustainable development. (September 2019) - Ukachi, Ngozi B; Anasi, Stella NI
Maternal and child mortality pose a great challenge in developing nations notwithstanding the robust initiatives instituted at both the global and national levels to ameliorate it. This study is aimed at ascertaining women's perception of the impact of information and communication technologies on access to maternal and child health information and its implication on sustainable development. The descriptive research design was adopted for the study. Purposive sampling technique was used in selecting University of Lagos Teaching Hospital and subsequently, the three clinics (Obstetrics and Gynaecology, Paediatrics Outpatient, and Antenatal clinics) where the needed groups could be seen. Questionnaire was the instrument used for data collection while SPSS statistical package was used for data analysis. The study revealed that the women perceive information and communication technologies to have a positive impact on their access to maternal and child health information while the key technological facilities used by the respondents in accessing maternal and child health information were mobile phones and social media tools such as Facebook, YouTube, blogs and Twitter. It was also found that irregular power supply, poor Internet access, and ignorance of the media that transmit maternal and child health information were the key factors that militate against effective access to maternal and child health information using communication technologies. The implication of this result on sustainable development is discussed and recommendations made.